APLIKASI MODEL KANO DALAM PENGUKURAN KUALITAS PERGURUAN TINGGI SWASTA KOTA PEKANBARU BERDASARKAN PERSPEKTIF MAHASISWA - Astri Ayu Purwati, Silvia Sari Sitompul (Fakultas Ekonomi Universitas Pasir Pengaraian, 2017)
Competition in the current era of Technology would require a country to be able to improve the quality of human resources and it is one of them obtained through improving the quality of education, especially higher education. The purpose of this research is to identify the priority quality attribute to be improved in accordance with customer expectation at Pekanbaru Higher Education and then take improvement step by creating a strategy and plan for attribute of quality that prioritized. The population in this study are 47 Higher Education in Pekanbaru. Selection of Higher Education sample is done by simple random sampling technique where there are 381 Students from 6 University of Pekanbaru choosed as sample. This research uses Kano Model. The result of the research shows that it is necessary to evaluate and improve the attributes that are in the one dimensional category. Among the attributes are 1) curriculum oriented to the diversity of fields of science, technology, field skills, and areas of professional proficiency 2) Textbooks, teaching materials / handouts can be well understood, 3) atmosphere learning process are fun, creative, interactive and motivate the students, 4) Interaction with lecturers outside class, 5) Academic information is easy to obtain, fast and accurate, 6) Selection of new student candidates is implemented selectively and quickly, 7) Online and manual service is effective and fast, 8) Classroom facilities (desk, chairs, blackboard, air conditioner , Infocus) is adequate, 9) Ease of internet access, 10) Availability of parker facilities, 11) Mastery of technological skills and english students.